SKRINING AKTIVITAS ANTIOKSIDAN, ANTIAGING DAN PENGHAMBATAN TYROSINASE DARI EKSTRAK ETANOLIK DAN ETIL ASETAT DAGING BUAH DAN KULIT BUAH LANGSAT (Lansium domesticum Corr) SECARA IN VITRO - Syamsu Nur; Rumiyati Rumiyati; Endang Lukitaningsih (Majalah Obat Tradisional, 2017)
This study aims to determine the bioactivity of L.domesticum as cosmetic ingredient. The extraction was prepared by maceration with ethanol 96 % and ethyl acetate to obtain ethanolic extract of fruit flesh (BLE), ethanolic extract of fruit peel (KLE), ethyl acetate extract of fruit flesh (KLE) and fruit peel (KLEA). Then, determination of compounds was conducted by thin layer chromatography (TLC) and analysed of total phenolic and flavonoid content with colorimetric method. The antioxidant capacity was measured using radical scavenging assay of 1,2-diphenyl-2-picrylhydrazyl (DPPH), β-carotene bleaching assay (BCB) and ferric reducing antioxidant power assay (FRAP). The inhibitory effect of skin degradation enzymes (anti-aging) was carried out using elastase and collagenase assay. The tyrosinase inhibitory effect was determined using mushroom tyrosinase. Based on TLC result, extract of L.domesticum containing phenolic, flavonoids, terpenoids and steroids compounds. The largest of total flavonoid content was obtained in KLE (4,76±0,26 %b/b EQ) and phenolic total content in BLEA (6,4±0,15 %b/b EG). Sequence of antioxidant activity measured using DPPH method was BLEA> KLE> BLE> KLEA; while using BCB method and FRAP method were respectively KLEA>BLEA> KLE> BLE; and BLEA> KLE> BLE> KLEA. KLE and KLEA extracts showed the most potent to remaining activity of the enzyme elastase and collagenase. In addition, BLE extract has the higest tyrosinase inhibition than others. Based on these results it can be concluded that the extracts of the fruit flesh and fruit peel of L. domesticum can be used as a cosmetic active ingredient for anti-aging and anti-tyrosinase.